Ben X - Khan, Praga; Balthazar, Nic 1964- (Kinowelt Home Entertainment - Arthaus, 2008)
An autistic teenager retreats into the world of online gaming, to escape bullying at school. With the help of a friend he meets online, he devises a plan to confront the bullies.
Bildformat 1.78:1 (anamorph)
Orig.: Belgien, Niederlande 2007
Enth. Making of ; alternative Szenen ; die Weltpremiere beim Filmfest Montréal ; Interviews ; Film-Einführung von Regisseur Nic Balthazar (Text) ; "Ben X" - eine wahre Lebensgeschichte (Text) ; Fotogalerie
Keywords: Asperger's syndrome -- Drama; Bullying in schools -- Drama; Computer games -- Drama; Revenge -- Drama; Feature films; Social problem films